The Therapeutic Potential of Targeting Cytokine Alarmins to Treat Allergic Airway Inflammation - Sy, Chandler B.; Siracusa, Mark C. (Frontiers in Physiology, 2016)
Asthma is a heterogeneous disorder that results in recurrent attacks of breathlessness, coughing, and wheezing that affects millions of people worldwide. Although the precise causes of asthma are unclear, studies suggest that a combination of genetic predisposition and environmental exposure to various allergens and pathogens contribute to its development. Currently, the most common treatment to control asthma is a dual combination of β2-adrenergic receptor agonists and corticosteroids. However, studies have shown that some patients do not respond well to these medications, while others experience significant side effects. It is reported that the majority of asthmas are associated with T helper type 2 (TH2) responses. In these patients, allergen challenge initiates the influx of TH2 cells in the airways leading to an increased production of TH2-associated cytokines and the promotion of allergy-induced asthma. Therefore, biologics that target this pathway may provide an alternative method to treat the allergic airway inflammation associated with asthma. As of now, only two biologics (omalizumab and mepolizumab), which target immunoglobulin E and interleukin-5, respectively, are FDA-approved and being prescribed to asthmatics. However, recent studies have reported that targeting other components of the TH2 response also show great promise. In this review, we will briefly describe the immunologic mechanisms underlying allergic asthma. Furthermore, we will discuss the current therapeutic strategies used to treat asthma including their limitations. Finally, we will highlight the benefits of using biologics to treat asthma-associated allergic airway inflammation with an emphasis on the potential of targeting cytokine alarmins, especially thymic stromal lymphopoietin.